Lethal and Sublethal Responses of Hydropsyche pellucidula (Insecta, Trichoptera) to Commercial Polypropylene Microplastics after Different Preconditioning Treatments - Manuela Piccardo; Marco Bertoli; Paolo Pastorino; Damià Barceló; Francesca Provenza; Davide Lesa; Serena Anselmi; Antonia Concetta Elia; Marino Prearo; Elisabetta Pizzul; Monia Renzi (Toxics, 2021)
Microplastics (MPs) pose biological and chemical hazards in aquatic and terrestrial food webs across the globe. Research on microplastic contamination has long focused on marine ecosystems, whereas the toxicological impact on freshwater organisms is still little explored. In this study, the lethal and sublethal response of the freshwater macroinvertebrate Hydropsyche pellucidula exposed to polypropylene MPs after different pre-conditioning treatments was assessed. Field samples were collected in a riverine system (Vipacco river; northeast Italy) to assess the characteristics of the MPs in the aquatic environment Both water and sediment were contaminated by MPs (3.73 ± 2.11 items m−3 per min and 3.33 ± 4.16 items dm−3, respectively). The chemical MPs composition included polystyrene, polyethylene terephthalate, polyurethane, polyamide, polypropylene, and polyethylene. Polypropylene (PP), although not the most abundant polymer recorded in the study area, was preferred over the other types according to its abundance in freshwater and H. pellucidula feeding behavior. A housing test was performed to recreate the natural conditions of larvae sampled for a reliable response to the ecotoxicological tests. The microplastics underwent either preconditioning with Vipacco River water (PP-river) and surfactant Triton X-100 (PP-sf) or no pre-treatment (PP). Submersion of microplastics in 10 µg L−1 of surfactant solution for 24 h was sufficient to induce consistent spectral changes and modify the chemical profile of the plastic surface. Mortality rate differed according to treatment: PP and PP-river > positive control > PP-sf > negative control. Integrated biomarker response (IBRv2) and analysis of oxidative stress biomarker levels showed a greater response of superoxide dismutase and lipid peroxidation (malondialdehyde) in larvae treated with PP conditioned in surfactant. Our findings enhance knowledge on the toxicity of PP and conditioning phases on H. pellucidula larvae.